Dual Commitment to Leader and Organization: Alternative Models Based on the Employees’ Emotional Awareness - Santana-Martins, Marisa (2022)
Management has been considering employee commitment as one of the strategic priorities, due to many studies suggesting the positive influence of commitment on high performance, innovative work behavior, employee retention, and many other important business outcomes. Nevertheless, commitment is considered an abstract construct, from which human resources management needs to create policies and practices that effectively support the business strategy and organizational culture. The existence of many foci of commitment in the workplace has been a challenge in that scenario, being important to understand how different foci relate to each other and how they influence the employee commitment process. To contribute to filling this gap, this research aims to compare two different models, analyzing the relationship between two foci of commitment, namely the affective commitment to the leader and organizational commitment. For this purpose, the employees’ emotional awareness has been considered as an independent variable. Hence, this study seeks to identify which model has higher explanatory power, and consequently, a more significant impact on the process of the employees’ commitment. The implications for theory and practice are discussed.